Discerning component traits contributing to specific water use in perennial ryegrass. Issue 4 (3rd September 2022) - Weerarathne, Visna; Garcia, Larissa; Carnevalli, Roberta; Fu, Bingzhe; Matthew, Cory
ABSTRACT: The productivity of perennial ryegrass ( Lolium perenne L.) is constrained by summer water deficit. We hypothesised that selection for desirable water relations traits might partially mitigate this constraint. Genotypes of a 1970s, and two recent ryegrass cultivars were grown in 55 cm tall pots for three months and exposed to moisture deficit for four weeks, then 66 plants were assessed for shoot (SDW) and root (RDW) dry weight, leaf elongation rate (LER), specific water use (SWU), leaf osmotic potential (OP), OP change, leaf relative water content (RWC), and gravimetric soil moisture. Among the 66 genotypes, SWU ranged from 935 ± 19 to 1754 ± 74 g H2 O g –1 DM. In principal component (PC) analysis, PC1 indicated greater growth and lower SWU from greater soil water extraction as the common trait association among genotypes tested and ANOVA of PC scores indicated that recent cultivars outperformed the 1970s cultivar. PC2 indicated water saving by decreased LER and SDW, with increased RDW indicative of summer dormancy. PC3 associated more negative OP with improved SWU and RWC. This experiment demonstrates not only genotypic diversity for SWU but also diversity in trait associations determining SWU, which should be considered when investigating SWU, both in ecology and agronomy research.